Hernioplasty with Laparoscopy Mesh Application in Equine with Incisional Hernia - Gomes, Anny Raissa Carolini; Rosa, Bruna Machado Amaral; Lorga, Andressa Duarte; Janiszewski, Jéssica do Rocio; Strugava, Lucimara; Schade, Jackson; Moreno, Juan Carlos Duque; Dornbusch, Peterson Triches (Acta Scientiae Veterinariae, 2021)
Background: Incisional hernia in the midline can be a consequence of abdominal surgeries, which incidence is around 5.7-18%. Surgical indication occurs in cases of large hernias, and the most common techniques used involve the closing of the musculature in a primary way, with sutures, and the implantation of a mesh on the abdominal wall. Laparoscopic hernioplasty emerged as a less invasive option, showing superiority when compared with open surgical techniques in human medicine, however there are few reports describing this technique in equines. So, the aim of this paper is to report a case of hernioplasty, using laparoscopic mesh, in a horse with midline incisional hernia. Case: A 13-year-old castrated male Brasileiro de Hipismo horse, weighing 415 kg, practitioner of classic equestrian, presented an incisional hernia after 14 days from an exploratory laparotomy surgery realized to treat colic syndrome. After 6 months, the patient was referred to a Veterinary Medicine Teaching Hospital for the correction of the defect in the abdominal wall. During palpation, the animal did not present local pain or other sign of inflammation, and the hernia measured approximately 20 cm in diameter. The animal was submitted to general anesthesia and placed in dorsal decubitus for the hernioplasty surgical procedure. An incision was made in cranial region of the midline, close to the xiphoid to introduce a single port; the abdomen was inflated with CO2 gas (12 mmHg) and the operating table was tilted in order to displace the organs cranially, facilitating the laparoscopic procedure. The abdomen was inspected and the presence of a single adherence could be observed, which was disrupted with endoscopic forceps. The mesh was introduced through the single port incision and anchored to the musculature, using polypropylene 2 following the marking points previously performed on the implant, covering the defect in the abdominal musculature. In the postoperative period, analgesia was instituted with non-steroidal anti-inflammatory drugs, antibiotic therapy with intravenous benzylpenicillin potassium+gentamicin sulfate, and daily dressings. The animal showed pain responsive to the instituted analgesia in the first 24-72 h after surgery. The discharge was established after 18 days of hospitalization with the recommendation of daily dressings and use of compressive bandage until the complete healing of the wound. Postoperative complications resulting from the laparoscopic hernioplasty technique was not observed in this case.The hernia reduction was satisfactory, with a good aesthetic result after five months, when the animal resumed its athletic activities. Discussion: Laparoscopy hernioplasty is poorly described in equine medicine, and there are no reports of this procedure performed in Brazil, however, it is widely used in human medicine with results superior to open hernioplasty techniques. In the present case and in others reported in the literature, the laparoscopic technique proved to be effective in reducing incisional hernias in horses. The animals had good regression of the hernia sac and the aesthetic result was satisfactory, with few post-surgical complications. In studies in which the open hernioplasty technique was used, there was a higher occurrence of complications, in addition to more intense pain resulting from the procedure and later return to athletic activity, demonstrating that the minimally invasive technique by video surgery can be advantageous.